2015
DOI: 10.1021/mp500764p
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Polyplex-Mediated Gene Transfection by Small-Molecule Regulators of Autophagy

Abstract: Nonviral gene transfection mediated by cationic polymer/DNA polyplexes often imposes stress and toxicity to cells. To better understand the relationship between cellular stress responses and polyplex-mediated transfection, polyplex-induced early autophagy in mouse fibroblasts was characterized and the impact of autophagy modulation on transgene expression evaluated. Transmission electron microscopy revealed the formation of double-membraned autophagosome in the cytoplasm of polyplex-transfected cells. Immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This ruffling, coupled with the blebbing and irregular morphologies observed in the confocal images of CT26 cells (Fig. 4), may suggest that CT26 cells are more sensitive to foreign materials than SK-BR3, and may be signs of nanomaterial induced cellular toxicity [20]. Lastly, the vesicles imaged in CT26 cells at the 24-h time point appear to contain both particle aggregates and cellular debris; this observation suggests that the cytoplasmic vesicles containing the AuPAMAM/DNA complexes may have degradative properties, or may be responsible for sequestering degraded material.…”
Section: Discussionmentioning
confidence: 99%
“…This ruffling, coupled with the blebbing and irregular morphologies observed in the confocal images of CT26 cells (Fig. 4), may suggest that CT26 cells are more sensitive to foreign materials than SK-BR3, and may be signs of nanomaterial induced cellular toxicity [20]. Lastly, the vesicles imaged in CT26 cells at the 24-h time point appear to contain both particle aggregates and cellular debris; this observation suggests that the cytoplasmic vesicles containing the AuPAMAM/DNA complexes may have degradative properties, or may be responsible for sequestering degraded material.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting emerging issue for both LNP and polyplex delivery is the potential role of autophagy. Thus, reports have indicated that damage to endosomes caused by delivery agents can trigger the autophagic process both for LPs and for polyplexes [37,51,52]. However, it is not clear to what degree autophagosome formation affects the functionality of the delivered oligonucleotide, with some reports indicating a significant effect via modulation of autophagy [51] and others indicating the opposite [37].…”
Section: Trafficking Of Oligonucleotides Associated With Other Nanoparticlesmentioning
confidence: 99%
“…Autophagy regulators 3-methyladenine (3-MA) and rapamycin were used in transfection studies as previously described. 27 Briefly, 3-MA was supplemented to Opti-MEM medium at 5 or 10 mM during the 4 hour transfection period. The complete media added after transfection did not contain 3-MA.…”
Section: Autophagy Regulation Treatmentsmentioning
confidence: 99%